2006
DOI: 10.1002/hep.21362
|View full text |Cite
|
Sign up to set email alerts
|

Human UDP-glucuronosyltransferase (UGT)1A3 enzyme conjugates chenodeoxycholic acid in the liver

Abstract: Chenodeoxycholic acid (CDCA) is a liver-formed detergent and plays an important role in the control of cholesterol homeostasis. During cholestasis, toxic bile acids (BA) accumulate in hepatocytes causing damage and consequent impairment of their function. Glucuronidation, a conjugation reaction catalyzed by UDP-glucuronosyltransferase (UGT) enzymes, is considered an important metabolic pathway for hepatic BA. This study identifies the human UGT1A3 enzyme as the major enzyme responsible for the hepatic formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
128
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(140 citation statements)
references
References 46 publications
10
128
2
Order By: Relevance
“…The thyroxine glucuronosyltransferase activity in microsomes from 12 human livers ranged from 23.7 to 84.8 pmol/ min/mg protein, representing 3.6-fold variability. Correlation analyses were performed between the thyroxine glucuronosyltransferase activity and typical activities including bilirubin O-glucuronidation catalyzed by UGT1A1, estradiol 3-O-glucuronidation catalyzed by UGT1A1 and UGT1A8 (Lepine et al, 2004), chenodeoxycholic acid 24-O-glucuronidation catalyzed by UGT1A3 (Trottier et al, 2006), imipramine N-glucuronidation catalyzed by UGT1A3 and UGT1A4, serotonin O-glucuronidation catalyzed by UGT1A6, propofol O-glucuronidation catalyzed by UGT1A8 and UGT1A9, or morphine 3-Oglucuronidation catalyzed by UGT2B7 (Table 3). Since UGT1A8 is not expressed in human liver, the estradiol 3-O-and propofol Oglucuronosyltransferase activities represented are the UGT1A1 and UGT1A9 activities, respectively.…”
Section: Kinetics Of Thyroxine Glucuronosyltransferase Activities Bymentioning
confidence: 99%
See 1 more Smart Citation
“…The thyroxine glucuronosyltransferase activity in microsomes from 12 human livers ranged from 23.7 to 84.8 pmol/ min/mg protein, representing 3.6-fold variability. Correlation analyses were performed between the thyroxine glucuronosyltransferase activity and typical activities including bilirubin O-glucuronidation catalyzed by UGT1A1, estradiol 3-O-glucuronidation catalyzed by UGT1A1 and UGT1A8 (Lepine et al, 2004), chenodeoxycholic acid 24-O-glucuronidation catalyzed by UGT1A3 (Trottier et al, 2006), imipramine N-glucuronidation catalyzed by UGT1A3 and UGT1A4, serotonin O-glucuronidation catalyzed by UGT1A6, propofol O-glucuronidation catalyzed by UGT1A8 and UGT1A9, or morphine 3-Oglucuronidation catalyzed by UGT2B7 (Table 3). Since UGT1A8 is not expressed in human liver, the estradiol 3-O-and propofol Oglucuronosyltransferase activities represented are the UGT1A1 and UGT1A9 activities, respectively.…”
Section: Kinetics Of Thyroxine Glucuronosyltransferase Activities Bymentioning
confidence: 99%
“…Bilirubin O-glucuronosyltransferase , imipramine N-glucuronosyltransferase , and serotonin O-glucuronosyltransferase (Fujiwara et al, 2007) activities in microsomes from 12 human livers were determined according to methods established in our laboratory. Chenodeoxycholic acid 24-O-glucuronosyltransferase activities in these human liver microsomes were determined according to the method of Trottier et al (2006) with slight modifications. Estradiol 3-O-, propofol O-, and morphine 3-O-glucuronosyltransferase activities in these human liver microsomes were provided by the manufacturer.…”
Section: Thyroxine Glucuronidation By Human Ugtmentioning
confidence: 99%
“…Hence, as shown in SHRSP and SHESP5/Dmcr male rats [18], these data suggest the importance of phase II reactions of drug-metabolizing enzymes in NASH/NAFLD progression and differing sensitivities to HFC feeding. UGT and SULT are involved in detoxification of toxic BAs such as CDCA and glyco-formed BAs [36,37], and whereas Ugt1a1 contributes to bilirubin metabolism, Ugt1a3, Ugt2b4, and Ugt2b7 metabolize BA (24-OH), BA (6-OH), and BA (3-OH), respectively, [38][39][40]. With the exceptions of Ugt1a3 and 2b7, the present HFC diet had smaller effects on UGT isoforms in female rats at early stages, and although the roles of Ugt1a6 in BA metabolism remain unknown, this isoform was relatively unaffected by HFC feeding in females.…”
Section: Discussionmentioning
confidence: 99%
“…This may also apply to other species with mixed taurine and glycine conjugation of BAs [13]. Other conjugation reactions such as sulfation and glucuronidation may occur, but are considered less relevant for the elimination of BAs under normal physiological conditions [14][15][16][17][18][19][20].…”
Section: Bile Acid Biosynthesis and Conjugationmentioning
confidence: 99%
“…Glucuronidation of BAs, for example, appears to be of little relevance under normal physiologic conditions [82]. However, it was reported that glucuronidation may become more important under severe cholestatic conditions, since it allows the conversion of cytotoxic BAs into non-toxic glucuronides, which also facilitates MRP3-mediated alternative efflux from hepatocytes into the blood for urinary elimination [16,[83][84][85]. Sulfation of BAs by sulfotransferase (e.g.…”
Section: Bile Acids As Key Players In Dilimentioning
confidence: 99%